Design and realization of light absorbers using plasmonic nanoparticles. (January 2019) - Escoubas, Ludovic; Carlberg, Miriam; Le Rouzo, Judikael; Pourcin, Florent; Ackermann, Jorg; Margeat, Olivier; Reynaud, Clement; Duche, David; Simon, Jean-Jacques; Sauvage, Rose-Marie; Berginc, Gérard
Abstract: The applications of light absorbers concern photodetectors, optical filters, solar applications or flexible electronics. In this review, we will detail the application of such light absorbers and we will develop the main demonstrations of the use of metallic nanoparticles embedded within a host matrix to fabricate coatings aiming at harvesting light. We will explain how chemically synthetized silver nanoparticles of various shapes (spheres, cubes, …) and sizes allow controlling the optical properties of heterogeneous thin film layers. By coupling the optical characterizations with computer modeling, we will describe how the nanoparticles behave both individually and collectively. To control reflected and absorbed light by thin film layers containing nanoparticles several points have to be addressed: the relation between the shape of the nanoparticle and the absorptance of the layer, the interaction of light between nanoparticles and the collective behavior of aggregates.